Legal Validity of HGB Extension Over Management Rights in Surabaya: Keabsahan Hukum Perpanjangan HGB di Atas Hak Pengelolaan di Surabaya - Erdianto, Dyta Widi; Raharja, Gede Dimas Bayu Hardi; Wicaksana, Satya Adi; Sofia, Arijna Nurin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Land tenure rights, particularly Building Use Rights (HGB) over Management Rights (HPL), play a crucial role in Indonesia’s legal and economic landscape.Specific Background: Extending HGB over HPL requires approval from the HPL holder, leading to legal disputes when HGB holders are unaware of their land’s status.Knowledge Gap: Limited studies address the legal mechanisms for extending HGB over HPL, especially after Government Regulation No. 18 of 2021.Aims: This study analyzes the legal framework for HGB extensions over HPL and examines legal remedies for unaware HGB holders.Results: Findings show that approval from the HPL holder is mandatory for HGB extensions, and without it, applications are rejected. Court rulings confirm this requirement.Novelty: This study clarifies recent regulatory changes and their impact on landowners.Implications: Clearer legal frameworks and better land status verification are needed to prevent disputes and ensure compliance. Highlights: Mandatory Approval: HGB extensions over HPL require approval from the HPL holder; otherwise, they are legally invalid. Regulatory Impact: Government Regulation No. 18 of 2021 reinforces strict conditions for HGB extensions, affecting landowners. Legal Remedies: HGB holders unaware of their land’s HPL status must pursue legal verification and compliance to secure extensions. Keywords: Extension of Term, Building Rights Title, Land Utilisation, Management Rights